A novel strategy to apply metallic nanoparticles to manufacture NiCrAl composite coatings smartly growing chromia and alumina. (1st April 2022) - Peng, Xiao; Zhen, Huijuan; Tian, Lixi; Wang, Xiaolan; Wang, Kai; Xie, Yun
Abstract: Formation of external scale rather than internal particles of chromia and alumina is of great importance for Cr- and Al-containing metallic materials to resist oxidation at high temperatures. Here we report a new strategy to apply metallic nanoparticles rich in Cr and Al to manufacture oxidation-resistant NiCrAl coatings with a well-designed structure, which can not only make the external oxide scale formation a quick and easy process but also be manufactured by simple electroplating and electrophorestic deposition following an established oxide map, so as to allow the composite coatings to smartly develop the best oxide scale against specific oxidizing environments. The method can be used to economically and systematically manufacture the MCrAlY (M = Ni, Co, or their combinations) coatings on superalloys and the metal-ceramic diffusion barriers between them.